AVALIAÇÃO DA ATIVIDADE ANTI-INFLAMATÓRIA TÓPICA DO COMPOSTO PELLEC1 ISOLADO DA Combretum leprosum - Brito, Priscilla Salles de (2012)
PelleC1 is an isolated compound from the Combretum leprosum (Combretaceae) that is a shrub popularly known as "mofumbo". This plant is used in folk medicine for wound healing, in the haemorrhages treatment or as a sedative. Researches with the extract of the plant attribute analgesic and anti-inflammatory activity to Combretum leprosum when orally administered. Based on these, the aim of this study was to evaluate the topical antiinflammatory effect of the PelleC1 compound in a skin chronic inflammatory model in mice. The anti-inflammatory activity of the PelleC1 was evaluated in the model of mice ear chronic inflammatory model induced by repeated applications of 12-O-tetradecanoilforbol acetate. The topical application of PelleC1 (0.3 mg/ear) caused a significantly inhibition of ear edema induced by TPA from the 6th day of the experiment (38.12 ± 6.89%) and this effect was intensified during the experiment until the last day (9th day, reduction of 62.44 ± 6.34%). The analysis of ears weight confirmed this result.The ears treated with PelleC1 or with dexamethasone (0.05 mg/ear) had a significant reduction of 30.17 ± 2.96% and 30.88 ± 1.80%, respectively, on weight of the ears, when compared with the control group (24.03 ± 1.65 mg). Another important event in the skin inflammation is the infiltration of polymorphonuclear and mononuclear cells, which were indirectly evaluated by determining the activity of enzymes myeloperoxidase (MPO) and n-acetyl-D-glucosaminidase (NAG). The studied compound reduced the activity of MPO and NAG, 31,45 ± 4,59% e 39,31 ± 0,64%, respectively, when compared to the controls (0,29 ± 0,01 DO/Biopsy - MPO; 1,73 ± 0,06 DO/Biopsy – NAG). The histological analysis confirmed this result and showed that compound PelleC1 and dexamethasone were able to reduce the thickness increase of the epidermis in 59,85 ± 5,05% e 60,10 ±3,77%, respectively, when compared to the control group (71,13 ± 4,21 μm). The PelleC1 and dexamethasone also showed a reduction in cell proliferation verified by immunohistochemistry for proliferating cell nuclear antigen of 71,7 ± 4,4% e 66,3 ± 0,5 respectively, when compared with the control group (156,4 ± 8,5 cells/field). The obtained results suggest that the PelleC1 has potent topical anti-inflammatory activity, since it reduced swelling, cell migration and proliferation in chronic inflammatory processes on the skin.